Connectivity with primary forest determines the value of secondary tropical forests for bird conservation - Mayhew,RJ; Tobias,JA; Bunnefeld,L; Dent,DH (Biotropica, 2019)
Species extinctions caused by the destruction and degradation of tropical primary forest may be at least partially mitigated by the expansion of regenerating secondary forest. However, the conservation value of secondary forest remains controversial, and potentially underestimated, since most previous studies have focused on young, single-aged, or isolated stands. Here, we use point-count surveys to compare tropical forest bird communities in 20–120-year-old secondary forest with primary forest stands in central Panama, with varying connectivity between secondary forest sites and extensive primary forest. We found that species richness and other metrics of ecological diversity, as well as the combined population density of all birds, reached a peak in younger (20-year-old) secondary forests and appeared to decline in older secondary forest stands. This counter-intuitive result can be explained by the greater connectivity between younger secondary forests and extensive primary forests at our study site, compared with older secondary forests that are either (a) more isolated or (b) connected to primary forests that are themselves small and isolated. Our results suggest that connectivity with extensive primary forest is a more important determinant of avian species richness and community structure than forest age, and highlight the vital contribution secondary forests can make in conserving tropical bird diversity, so long as extensive primary habitats are adjacent and spatially connected.Abstract in Spanish is available with online material.